PENERAPAN PEMBELAJARAN MULTIMEDIA INTERAKTIF POWTOON UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA SEKOLAH DASAR - Amalia, Nur Afriani; Kaddas, Badruddin; Irviana, Ira (Phinisi Integration Review, 2024)
This research aims to determine (1) the application of video-based interactive multimedia learning media assisted by the Powtoon application in science subjects (2) improving student learning outcomes through video-based interactive multimedia learning media assisted by the Powtoon application in science subjects for elementary school students. This research uses Classroom Action Research. The research objects are Class V elementary school students. Data sources in this research are interviews, observations, tests and documentation. The data in this research were analyzed using descriptive quantitative statistical analysis. Based on the research that has been carried out, the results obtained (1) through the application of Powtoon media can help teachers create interesting, unique and interactive learning media in the classroom learning process (2) Based on the results of the first cycle and second cycle tests, namely, from 25 students declared to meet the KKM. This research has implications that through the application of video-based interactive multimedia learning media, learning in the classroom takes place actively and interactively, students appear more enthusiastic and motivated to pay attention to what is displayed and explained directly by the teacher. This can certainly improve student learning outcomes, especially in Natural Sciences (Science) subjects.Penelitian ini bertujuan untuk mengetahui (1) penerapan media pembelajaran multimedia interaktif berbasis video berbantuan aplikasi powtoon pada mata pelajaran IPA (2) peningkatan hasil belajar siswa melalui media pembelajaran multimedia interaktif berbasis video berbantuan aplikasi powtoon pada mata pelajaran IPA Siswa Sekolah Dasar. Penelitian ini menggunakan Penelitian Tindakan Kelas. Adapun objek penelitiannya adalah siswa Kelas V Sekolah Dasar. Sumber data dalam penelitian ini adalah wawancara, observasi, tes dan dokumentasi. Data dalam penelitian ini dianalisis menggunakan analisis statistic secara kuantitatif deskriptif.  Berdasarkan penelitian yang telah dilakukan memperoleh hasil (1) melalui penerapan media powtoon dapat membantu guru dalam membuat media pembelajaran yang menarik, unik dan interaktif di dalam proses pembelajaran di kelas (2) Berdasarkan hasil tes siklus I dan siklus II yaitu, dari 25 orang siswa dinyatakan memenuhi KKM. Penelitian ini berimplikasi pada melalui penerapan media pembelajaran multimedia interaktif berbasis video, pembelajaran di dalam keilas beirlangsung seicara aktif dan inteiraktif siswa teirlihat leibih antusias dan teirmoitivasi untuk meimpeirhatikan apa yang ditampilkan dan dijeilaskan seicara langsung oileih guru. Hal ini tentunya dapat meningkatkan hasil belajar siswa khususnya pada mata pelajaran Ilmu Pengetahuan Alam (IPA).